Derive the consumer’s direct utility function if his indirect utility function has the form

$$v(\boldsymbol{\mathbf{p}},y)=yp_1^\alpha p_2^\beta$$

where $\beta ,\alpha$ are negative.


closed as off-topic by luchonacho, Giskard, Herr K., Adam Bailey, jmbejara May 18 '17 at 0:31

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question does not meet the standards for homework questions as spelled out in the relevant meta posts. For more information, see our policy on homework question and the general FAQ." – luchonacho, Giskard, Herr K., Adam Bailey, jmbejara


Use Roy's identity to find demand functions: $$\displaystyle x_1=-\frac{\frac{\partial v}{\partial p_1}}{\frac{\partial v}{\partial y}} =-\frac{\alpha yp_1^{\alpha-1} p_2^\beta}{p_1^\alpha p_2^\beta}=-\frac{\alpha y }{p_1} $$

$$\displaystyle x_2=-\frac{\frac{\partial v}{\partial p_2}}{\frac{\partial v}{\partial y}} =-\frac{\beta yp_1^{\alpha} p_2^{\beta-1}}{p_1^\alpha p_2^\beta}=-\frac{\beta y }{p_2} $$

Since $p_1x_1 + p_2x_2 = y$, from the above demand expressions we get $-\alpha -\beta = 1$. Demand equations above can also be rewritten as:

$$x_1^{-\alpha} = (-\alpha y)^{-\alpha}p_1^\alpha$$ $$x_2^{-\beta} = (-\beta y)^{-\beta}p_2^\beta$$

Multiplying them we obtain the following: $$x_1^{-\alpha}x_2^{-\beta} = (-\alpha y)^{-\alpha}p_1^\alpha (-\beta y)^{-\beta}p_1^\beta = (-\alpha)^{-\alpha}(-\beta)^{-\beta}yp_1^\alpha p_2^\beta $$

Comparing it with the indirect utility function, we get the direct utility function as:

$$u(x_1, x_2) = \frac{x_1^{-\alpha}x_2^{-\beta}}{(-\alpha)^{-\alpha}(-\beta)^{-\beta}}$$


Not the answer you're looking for? Browse other questions tagged or ask your own question.